Hygienic and sanitary conditions of commercialized sugarcane juice in Teresina – Piauí - Bacelar, Bacelar; Xavier, Cícero; Santos, Eldo; Ianiceli, Juliana; Brito, Mariana; Muratori, Maria (Pubvet, 2018)
Brazil is a major producer of sugar cane; its juice is extracted by means of mechanical or manual grinding. Often the manipulators perform other functions concomitantly, representing one of the means of contamination. In view of this, contamination by microorganisms and soils, from transport and storage to consumption, may result from inadequate conditions. The objective of this study was to evaluate the hygienic and sanitary conditions of cane juice marketed in Teresina, PI. Samples were obtained from randomly selected establishments. Nine samples of cane juice were collected in nature, three in each establishment and nine industrialized samples purchased in a single establishment, of the same brand, three samples each day, making a total of 18 samples. In the samples in nature, coliforms were present at 35ºC and at 45ºC and absence of Salmonella spp in all samples. In the analyzes of the industrialized broth no coliforms were found at 35ºC and at 45ºC, as well as Salmonella spp in none of the samples. The satisfactory sanitary and sanitary conditions of cane juice commercialized in Teresina, PI, depends on the establishment and if it is industrialized.